Character Education Through the Application of Ecological Architecture: A Case Study of Vocational High School in South Tangerang - Fasikhi Fasikhi; Uli Ratna Muliawat; Sulastri Sulastri; Somariah Fitriani (STAI Hubbulwathan Duri, 2023)
Schools with ecological architecture insight contribute to the surrounding environment, which has an impact on developing the character of students, such as increasing awareness of a sustainable environment. Therefore, the aim of this research is to examine whether the vocational high school in South Tangerang City, which is labelled as Adiwiyata (ideal environment) at the national level, has incorporated the principles of ecological architecture that take into account the surrounding environment, human movement, road circulation, drainage system, and noise level. In addition, this study also aims to explore whether the inculcation of character education has been implemented in habituation activities in schools. The research employed a case study research design, where the unit of analysis under study was one of the public schools in South Tangerang City, which had received a national-level Adiwiyata school award. Direct observation and interviews were used to gather the data. Interviews were conducted to the school principal, heads of study programs, teachers, and 24 students. This study revealed that the principles of ecological architecture principles were adhered in this school. In addition, the findings indicated that character development through character education is incorporated into all subjects as well as into well-executed routine activities, like the activity of “laskar hijau” (the green army), which teaches pupils to appreciate and maintain a beautiful school environment as a means of developing a sense of environmental responsibility.